3D numerical simulation of a Coulter counter array with analysis of electrokinetic forces - Pui, Tze Sian (2013)
Coulter counters have played an important role in biological cell assays since their introduction decades ago. Several types of high throughput micro-Coulter counters based on lab-on-chip devices have been commercialized recently. In this paper, we propose a highly integrated micro-Coulter counter array working under low DC voltage. The real-time electrical current change, including the pulse amplitude and width, of the micro-Coulter counter with novel structure is systematically investigated numerically. The major types of forces exerted on the particle in the micro-Coulter counter, including hydrodynamic force and electrokinetic force are quantitatively analyzed. The simulation in this study shows the pulse profile, such as width and amplitude, is affected by both particle size and the flow condition. The special cases of multiple particle aggregation and cross-talk between neighboring channels are also considered for their effects on the electric current pulses. This simulation provides critical insight and guidance for developing next new generations of micro-Coulter counter.